Potential of coal bottom ash as fine aggregates in the production of lightweight brick / Mohd Fadzil Arshad ... [et al.] - Arshad, Mohd Fadzil; Ahmad Zailani, Warid Wazien; Fauziah, Salmia Beddu; Abdullah, Sofian; Adesina, Adeyemi; Suryanita, Reni (2022)
The use of coal bottom ash, a by-product from the coal burning process in lightweight bricks production is getting more attention worldwide including in Malaysia. The main objective of this research is to assess the extended potential of bottom ash to produce lightweight bricks. The green technology-based lightweight bricks in this study are designed using the by-product resulting from the burning of pulverized coal in thermal power plants for electric power generations. The burning of pulverized coal was questioned extensively over the last decades due to the carbon dioxide emission which is about 2.0 billion tons annually. These lightweight bricks are produced from the combination of specifically graded bottom ash, classified pozzolanic ashes, fine aggregates, Ordinary Portland Cement, and water. The lightweight bricks were subjected to a few laboratory assessments including compressive strength test, density test, and water absorption test. It was observed that the C2 brick and C3 brick at 60% and 100% addition of bottom ash, respectively had comparable compressive strength with other commercialized bricks (cement-sand brick and clay brick). The addition of coal bottom ash also produces the lowest density of the bricks which is about 1.2 kg/m3 . Comparison with other commercialized bricks available in the market in terms of compressive strength, density, and water absorption indicated that the bottom ash-based bricks are stronger and lighter. A comprehensive selection of good quality materials and the selected mix design produced an acceptable quality of bricks that can be considered as part of the actual construction materials. Thus, with the production of this light and strong brick, the volume of the coal ash waste that was dumped in the landfill will be substantially reduced and simultaneously the lighter bricks will reduce the dead loads supported by the main structures of the building.